RANCANG BANGUN PROTOTYPE SISTEM SMART PARKING BERBASIS ARDUINO DAN PEMANTAUAN MELALUI SMARTPHONE - Rudi Rudi; Irwan Dinata; Rudy Kurniawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2017)
This design Smart Parking aims to design a microcontroller device that is Smart Parking that can inform and direct the driver to the empty parking area. The parking lot used as the research object consists of several parking locations with the capacity of several vehicles, but this study only selects some parking slots as samples. In this design has several common parts used, namely ultrasonic sensors HC-SR04, Arduino Mega, PC / laptop, LCD (Liquid Cristal Display) and IOT (Internet Of Things) research indicates that the LCD will show several parking slots already occupied and Some empty parking slots and monitoring via Smartphone using the Blynk app. As for the crossbar entrance of the parking area using a tool that is servo, and Arduino UNO as the operation of the parking doorstop. In this design the distance of the parking sensor below 6cm indicates that parking slots are occupied and above 6cm indicating the parking slot conditions available on LCD and Blynk applications. As for servo bar entry detects the car at a distance below 5cm servo will open with delay of 3 seconds and if above 5cm indicates that there is no car in front of the sensor bar.